Money Politics Sebagai Akar Permasalahan Demokrasi Indonesia: Tinjauan pada Pemiluh 2019 dan 2024 - Abraham, Agustinus (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This research examines money politics as a root problem in Indonesia’s democratic system, focusing on the 2019 and 2024 general elections. Money politics refers to the practice of distributing cash or goods by candidates, campaign teams, or volunteers to influence voters’ political choices. This study employs a qualitative method with a literature study approach to analyze several cases that occurred across different regions in Indonesia. The findings reveal that money politics was widespread during both elections, with the main modus operandi involving the distribution of cash, basic goods, and facilities. This practice not only violates the principles of free and fair elections but also undermines citizens’ dignity, weakens popular sovereignty, and serves as a major driver of political corruption. Contributing factors include power ambition, vulnerable economic conditions, low political education, weak oversight, and entrenched transactional political culture. To address this issue, the research highlights the importance of political party reform and strengthening democratic education, particularly through civic education programs. These efforts aim to increase political awareness among citizens and improve the overall quality of Indonesia’s democracy.